PENGARUH DIABETES SELF MANAGEMENT EDUCATION (DSME) BERBASIS APLIKASI WHATSAPP TERHADAP SELF EFFICACY PADA PASIEN DM TIPE 2 DI PUSKESMAS HAMPARAN PERAK - Agnes Silvina Marbun; Rinco Siregar; Karnirius Harefa; Theresia Yuni Florensia Sinabutar (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Diabetes mellitus (DM) is one of the biggest health problems in the world because every year there is an increase in cases. In addition to the increasing number, DM is also known to cause many complications which are divided into two, namely acute complications and chronic complications. The emergence of complications and leading to death in DM patients is due to the low self-efficacy and self-care behavior of DM patients themselves. Self-efficacy is an important factor that is defined as a patient's confidence in maintaining and improving his medical condition. Seeing the importance of self-efficacy in the care of DM patients, increasing patient self-efficacy is needed, namely through the Diabetes Self Management Education (DSME) program. The purpose of this study was to determine the effect of the WhatsApp-based DSME application on the self-efficacy of Type 2 DM patients. This type of research is a Quasy Experiment and the sampling technique used in this study is purposive sampling (Non-Probability sampling). The research design used was Pre-Experiment With Only one Group Pretest - Postest Design. The number of samples was 22 DM type 2 patients. Demographic data collection through questionnaires distributed via google form. The statistical test used was the Paired t test. The results of statistical tests found that there was an effect of WhatsApp-based DSME on the self-efficacy of Type 2 DM patients, with a p value of 0.000 (p <0.05). This shows that there is an effect of WhatsApp-based DSME on the self-efficacy of Type 2 DM patients at the Hamparan Perak Community Health Center.